Religious Power Struggle and Cembengan Tradition in Madukismo Sugar Factory Yogyakarta - Abdul Qodir Shaleh; Saifudin Zuhri; Ilyya Muhsin (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2020)
As an entity famous for its mystical synthesis, Yogyakarta Palace can harmonize between mysticism and religious and social expressions. This is represented in, one of them, Madukismo Sugar Factory in Yogyakarta, a sugarcane processing factory owned by Yogyakarta Palace. In its processing, there is one of local wisdom that reflects the existence of this mystical synthesis, namely Cembengan tradition. From it, arises a power struggle between orthodoxy and heterodoxy, bearing in mind that this factory is a public company which naturally comes from various religious groups. The main problems: how Cembengan tradition in Madukismo Sugar Factory in Yogyakarta is and how the struggle for religious power in Cembengan tradition is. This paper aims to find out Cembengan tradition and the struggle for the religious power that exists in the tradition. This study uses discursive action model as its approach. The research data were analyzed qualitatively using interview and literature study techniques. It was found that in Cembengan tradition, there is a tradition with a variety of activities, which is essentially asking for safety and blessing. The uniqueness is in the series of activities, there are istigotsah and pilgrimage to the tomb of the ancestor together, which is in series with the procession of Labuhan Laut, sugarcane bride and groom parade, and puppet show. This certainly gives rise to a power struggle between orthodoxy and heterodoxy, bearing in mind that Yogyakarta itself is the orthodox Islamic base as well as strong heterodoxy bases. However, Cembengan tradition continues because there are various things that are proven to occur and determine the quality of works and production results from Madukismo Sugar Factory itself. We can conclude that no matter how strong the struggle is, the mystical synthesis is still ongoing.